2018
DOI: 10.1002/celc.201701341
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Hollow CeO2/CePO4 with Nitrogen and Phosphorus Co‐Doped Carbon Shells for Enhanced Oxygen Reduction Reaction Catalytic Activity

Abstract: Achieving active and sustainable electrocatalysts for the oxygen reduction reaction with low cost and high performance attracts great interest in the field of fuel cells. Here, we report a facile route to prepare hollow CeO2/CePO4@N,P co‐doped carbon by pyrolyzing CeO2@polyaniline obtained in the presence of phytic acid. By virtue of the co‐doping of N and P elements as well as the existence of oxygen vacancies and the formation of a void, the product illustrated excellent catalytic activity towards the oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…The size of a single Co nanoparticle was ∼15 nm, and the thickness of the carbon layer was about 2–5 nm. Similar carbon encapsulated CeO 2 structures have been extensively reported in literature as ORR catalysts . It is believed that such thin layer carbon coating will not affect the oxygen sorption severely .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The size of a single Co nanoparticle was ∼15 nm, and the thickness of the carbon layer was about 2–5 nm. Similar carbon encapsulated CeO 2 structures have been extensively reported in literature as ORR catalysts . It is believed that such thin layer carbon coating will not affect the oxygen sorption severely .…”
Section: Resultssupporting
confidence: 81%
“…The well‐defined cathodic peaks of CeO 2 ‐600, NC‐CeO 2 and 0.5Co‐NC‐CeO 2 were at 0.620 V, 0.602 V and 0.827 V (vs. RHE), respectively. Specifically, the shape of the CV curve of 0.5Co‐NC‐CeO 2 was similar to that in the reference . The linear sweep voltammetry (LSV) at a rotating rate of 1600 rpm in O 2 ‐saturated 0.1 M KOH electrolyte was also performed.…”
Section: Resultsmentioning
confidence: 99%
“…[24] The C1s spectrum ( Figure 3c) shows four specific peaks located at 281.6 284, 284.6 and 285.3 eV, corresponding to CÀ Fe, sp 2 CÀ C, sp 3 CÀ C and CÀ N bonding, respectively. [25] The O 1s spectrum ( Figure 3d) can be deconvoluted into three peaks at 529.7, 531.9 and 532.8 eV, which can be attributed to O γ , O β , O α , respectively, [3] and the percentage of O β is 50.67 %. It has been accepted that O β , the chemisorbed oxygen, is closely related to make a great contribution to the ORR catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the oxygen reduction reaction is widely used, its reaction process is complicated and the kinetic reaction process is slow, which has always restricted its development. Up to now, Pt and Pt alloys displaying high catalytic activity are still recognized as the best candidates to accelerate ORR, but the high price, poor stability and low reserves of Pt hinder the commercial application of Pt‐based catalysts . Therefore, it is highly necessary to find highly stable electrocatalysts with low cost and abundant reserves.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, introducing N-doped carbon shells is an emerging strategy to resist coalescence of NPs. [28][29][30][31][32][33][34][35] Hyeon and co-workers have successfully synthesized 6.5-nm-sized PtFe iNPs coated by N-doped carbon shell derived from polydopamine. [31] Wei et al also demonstrated that the N-doped porous carbon shells can effectively impeding the migration and aggregation of Pt nanocrystals even at a heat-treatment temperature of 900°C.…”
Section: Introductionmentioning
confidence: 99%